Penguatan Logistik Kebencanaan Melalui Pelatihan Lokasi Gudang Berbasis Risiko Tsunami di Banten - Saribanon, Euis; Pratiwia, Sekar Widyastuti; Setiawan, Edhie Budi; Marina, Sandriana; Sihombing, Sarinah (Jurnal Abdimas Transportasi & Logistik, 2024)
The Banten region is one of the disaster-prone areas in Indonesia, particularly vulnerable to tsunamis, making the selection of warehouse locations a critical aspect in supporting effective emergency response. The accuracy of warehouse placement directly influences the speed of aid distribution and the security of supplies from potential secondary disasters. This community service activity aimed to enhance the capacity of MDMC Banten volunteers in understanding the principles of safe, efficient, and risk-based warehouse site selection. The activity was carried out through several stages, including the identification of existing conditions, conceptual socialization, real-case discussions in the Banten region, and spatial simulations using topographic maps and tsunami scenarios. The results showed significant improvement in participants’ understanding of the functional differences between main and transit warehouses, as well as their ability to evaluate locations based on risk and accessibility criteria. This program also produced strategic location recommendations tailored to the local geographic context. In conclusion, the risk-based educational approach combined with spatial simulation has proven effective in strengthening community-level disaster logistics planning capacity, particularly in high-risk regions such as Banten.